2021
DOI: 10.1519/jsc.0000000000003167
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Inflammation, Cardiac, and Muscle Damage Biomarkers After Running a Marathon

Abstract: Please confirm the given names (pink) and surnames (blue) of authors have been identified correctly. Please check and confirm whether all authors and their respective affiliations are appropriate. AU1) Please note that running head has been taken from the provided PDF. Please check and correct if necessary. AU2) Please check and confirm the edit made to the article title. AU3) Please check the edits made to the author name "Carlos Hernando-Domingo." AU4) Please provide city name and country for all affiliation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 43 publications
1
39
0
3
Order By: Relevance
“…Bernat-Adell et al [23] have discovered that within 24 and 48 h following marathon, athletes' serum CRP levels were significantly higher than those before exercise. Among the other biochemical indicators, we also found that homocysteine tended to be elevated following the exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Bernat-Adell et al [23] have discovered that within 24 and 48 h following marathon, athletes' serum CRP levels were significantly higher than those before exercise. Among the other biochemical indicators, we also found that homocysteine tended to be elevated following the exercise.…”
Section: Discussionmentioning
confidence: 99%
“…CK peaked at post-race among UT runners and decreased at 24 h post-race, while LT runners showed an increase in CK from post-race to 24 h post-race. Previous studies on half and full road marathons have reported peak values of CK at 24-h post-race [ 31 , 49 ]; while following longer MUM (i.e., 166-km), peak CK has been described to occur immediately post-race [ 4 , 50 ]. In addition, during a flat 200-km race CK was reported to significantly increase from 19-fold pre-race value at mid race to 90-fold pre-race value at the end of the race [ 51 ]; similarly, a continuous rise in CK has been described during a 217-km MUM [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples were collected from an antecubital vein by venipuncture using BD Vacutainer PST II tubes. Samples were centrifuged at 3500 rpm for ten minutes and kept at 4°C during transport to Vithas Rey Don Jaime Hospital (Castellon), where they were processed using the modular platform Roche / Hitachi clinical chemistry analyzer Cobas c311 (Roche Diagnostics, Penzberg, Germany), as previously published [ 13 , 31 , 32 ]. Biochemical results obtained immediately post-race were adjusted by employing the Dill and Costill method [ 33 ], using hematocrit and hemoglobin to determine the magnitude of plasma volume changes after the race in each participant [ 33 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Long‐distance endurance running, such as a marathon, can result in a range of signs and symptoms associated with exercise‐induced muscle damage (EIMD). A reduction in functional performance, strength loss, soreness, inflammation, and oxidative stress have all been reported following marathon running 1–6 . Similarly, the deleterious effects of EIMD following a bout of unaccustomed eccentrically biased exercise are well documented 7 .…”
Section: Introductionmentioning
confidence: 97%
“…In contrast, even the most elite, experienced, and well‐trained runners are not spared from the symptoms of EIMD 5 . Following a marathon run, muscle, cardiac, and inflammatory markers have been reported to remain elevated at day eight 1 and the repair of focal muscle fiber damage has been reported to take up to eight weeks 11 . Ultimately, timely recovery from the symptoms associated with EIMD is critical.…”
Section: Introductionmentioning
confidence: 99%